Industrial policies, patterns of learning and development: An evolutionary perspective - Mario Cimoli; Giovanni Dosi; Xiaodan Yu (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
This paper investigates the extent to which international trade hinges onpatents. We analyze the export and patenting activities of the universe of French exporting firms over the period 2002-2011. The noticeable feature of our study is that we observe export and patenting activities worldwide and at the product level. We exploit how heterogeneity of patent coverageacross (and within) product-country relates to exports. We find a patent premium of at least 10 percent, which is mainly associated with a quantity effect. A modest price effect emerges in specific sectors, notably pharmaceuticals. This work discusses the role of industrial policies within an evolutionary view of innovation and learning as drivers of economic development. Building on the notions of technological paradigms and trajectories, it links the processes of catching-up with the dynamics of capability accumulation within and across firms. In turn such processes are embedded in broader national systems of innovation wherein industrial policies play a pivotal role.
Keywords: O14; O30; O53; O54; 330; Technological paradigms; Catching up; Theory of production; Absolute and Comparative Advantages; National systems of innovation; Industrial Policies; Economic Evolution and Development